2011
DOI: 10.1007/s00248-011-9995-4
|View full text |Cite
|
Sign up to set email alerts
|

Burning Fire-Prone Mediterranean Shrublands: Immediate Changes in Soil Microbial Community Structure and Ecosystem Functions

Abstract: Wildfires subject soil microbes to extreme temperatures and modify their physical and chemical habitat. This might immediately alter their community structure and ecosystem functions. We burned a fire-prone shrubland under controlled conditions to investigate (1) the fire-induced changes in the community structure of soil archaea, bacteria and fungi by analysing 16S or 18S rRNA gene amplicons separated through denaturing gradient gel electrophoresis; (2) the physical and chemical variables determining the imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 57 publications
(102 reference statements)
8
80
0
2
Order By: Relevance
“…Other studies have reported similar trends in a laboratory heating experiment (Hatten and Zabowski, 2009), an experimental fire in Mediterranean shrublands (Goberna et al, 2012), a prescribed fire in a wooded-shrubland in Nevada, USA (Chief et al, 2012), and a ponderosa pine/Douglas fir wildfire in Colorado, USA (Ferrenberg et al, 2013). Our results also showed that the decreases in GWC, OM, and TKN in the organic horizon soils persisted up to 25 months post-fire, suggesting that the recovery of soil physical and chemical properties after a wildfire may be slow.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Other studies have reported similar trends in a laboratory heating experiment (Hatten and Zabowski, 2009), an experimental fire in Mediterranean shrublands (Goberna et al, 2012), a prescribed fire in a wooded-shrubland in Nevada, USA (Chief et al, 2012), and a ponderosa pine/Douglas fir wildfire in Colorado, USA (Ferrenberg et al, 2013). Our results also showed that the decreases in GWC, OM, and TKN in the organic horizon soils persisted up to 25 months post-fire, suggesting that the recovery of soil physical and chemical properties after a wildfire may be slow.…”
Section: Discussionmentioning
confidence: 53%
“…Several recent studies have shown declines in total soil microbial biomass in the mineral horizon after a fire (Choromanska and DeLuca, 2001;Yeager et al, 2005;Smith et al, 2008;Dooley and Treseder, 2012) while others have reported increases in microbial biomass post-fire (Goberna et al, 2012) or no significant difference in microbial biomass between non-burned and burned soils (Hamman et al, 2007). Similarly bacterial community structure in the mineral horizon has also been shown to be sensitive to fire, as exemplified with an experimental fire in a Mediterranean shrubland, which revealed a shift in bacterial community structure (Goberna et al, 2012). Related studies have revealed bacterial diversity decreases after a wildfire of red pine in Japan (Mabuhay et al, 2006) and after prescribed burning of an upland oak forest in the USA (Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrasting results about the effects of fire on ammonia oxidising microorganisms and nitrification have been published. At the short-term, fires have neither effects on nitrifiers (Acea and Carballas 1996) nor on ammonia oxidising archaea (Goberna et al 2012), despite burning that altered the community structure of all archaea, bacteria and fungi, as well as microbial biomass and activity (Barreiro et al 2010;Díaz-Raviña et al 1996;Goberna et al 2012). At the long-term, nitrifier abundance was increased by the fires (Acea and Carballas 1996;Ball et al 2010).…”
Section: Discussionmentioning
confidence: 93%
“…Despite the short terms effects, all these studies found that the influence of fire history on nematode community was undetectable in the long term (Renčo and Č erevková 2015). Similarly, De Marco et al (2005) and (Docherty et al 2012;Goberna et al 2012) found that the effects fire has on soil biochemistry and microbial communities were undetectable 33 months after a fire. There is clearly, then, the possibility of patterns in nematode diversity and community structure that exist beyond the effects of fire, perhaps influenced by underlying habitat and soil factors.…”
Section: Introductionmentioning
confidence: 89%